The Role of the Office of Cooperatives, MSMEs, and Labor in Empowering Micro, Small, and Medium Enterprises in Palu City (Evidence from 2022) - Yanti, Ulfi; Lutfi, Muthar; Jokolelono, Eko; Mangun, Nudiatulhuda; Achmad, Nuryana Haprin Dj (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
MSMEs are vital to Indonesia's economy, making a substantial contribution to GDP and employment. Nevertheless, a number of MSME players encounter obstacles such restricted capital availability, weak financial management abilities, and a lack of appropriate business mentoring. This study aims to analyze the role of the Cooperative, MSME, and Labor Department of Palu City in empowering Micro, Small, and Medium Enterprise (MSME) actors in 2022. The method used is descriptive with a qualitative approach. Data sources in this study consist of primary and secondary data. Primary data was obtained through direct interviews with staff of the Cooperative, MSME, and Labor Department of Palu City who work in the MSME field. Secondary data was obtained from official documents and archives (RSIP) owned by the department, particularly those related to MSME empowerment programs. Data collection techniques used include interviews, documentation, and collection of related documents from relevant agencies. Research results show that the Cooperative, MSME, and Labor Department of Palu City has implemented various empowerment programs, such as providing equipment and capital assistance, as well as business mentoring. The total business capital funds distributed to 1,101 MSME actors reached Rp2,202,000,000, and equipment assistance was adjusted according to each type of business. This program positively impacts MSME growth and poverty reduction in Palu City, despite challenges like low awareness of training, uneven mentoring, and limited capacity in business management and financial recording. Therefore, more intensive, integrated, and sustainable empowerment strategies are needed to optimally improve MSME capacity and competitiveness.